Divergent functional trajectories of frugivorous bird assemblages across restoration strategies driven by time and landscape context - Pedro Luna; Juan E. Guevara-Andino; Betzabet Obando-Tello; H. Martin Schaefer; Nico Blüthgen (Biological Conservation, 2026)

Oceanographic and climatic controls of meteoric 10Be fluxes to seafloor sediments: A global synthesis - Jennifer Middleton; Frank Pavia; Robert Anderson; Roseanne Schwartz; Martin Fleisher; Yong Lao; Yuxin Zhou; Christopher Kinsley; Joerg Schaefer; Martin Frank; Gisela Winckler (Quaternary Science Reviews, 2026)

From agriculture back to tropical rainforest: When does ecological succession stabilize hot and dry extremes? - Felicity L. Newell; Edith Villa-Galaviz; Constance J. Tremlett; Sebastián Escobar; Adriana Argoti; Nicole Büttner; Julio Carvajal; María F. Checa; Katrin Krauth; Gustavo Pazmiño-Otamendi; Karen M. Pedersen; Bryan Tamayo; et al. (Agricultural and Forest Meteorology, 2026)

Recovery of tree-related microhabitats in a tropical rainforest after agricultural abandonment - Ronja Hausmann; Sebastián Escobar; Nico Blüthgen; H. Martin Schaefer; Felicity L. Newell; Maria-José Endara; Juan Ernesto Guevara-Andino; Heike Feldhaar; Daniel Kraus; Dominik Thom; Jörg Müller (Biological Conservation, 2026)

Restoration legacy, landscape context and elevation shape frugivory in a tropical landscape - Pedro Luna; Juan E. Guevara-Andino; Betzabet Obando-Tello; Leonela E. Dávila-Narváez; H. Martin Schaefer; Nico Blüthgen (Biodiversity and Conservation, 2026)

Paired terrestrial cosmogenic nuclides support the mapping of relict polythermal terrains under the Keewatin Ice Divide, central mainland Nunavut, Canada - Isabelle McMartin; Pierre-Marc Godbout; Tommy Tremblay; John C. Gosse; Janet E. Campbell; Martin Roy; Joerg M. Schaefer; Iyse Randour (Quaternary Science Reviews, 2025)

HESI GTTC ring trial: Concordance between Ames and rodent carcinogenicity outcomes for N-nitrosamines (NAs) with rat and hamster metabolic conditions - Joel Bercu; Alejandra Trejo-Martin; Connie Chen; Maik Schuler; Jennifer Cheung; Tetyana Cheairs; Anthony M. Lynch; Dean Thomas; Andreas Czich; Aisar Atrakchi; Timothy J. McGovern; Robert H. Heflich; et al. (Regulatory Toxicology and Pharmacology, 2025)

Understanding the environmental impacts of residential water consumption in Brazil: Integrating the building stock with life cycle assessment - Igor Catão Martins Vaz; Enedir Ghisi; Taylana Piccinini Scolaro; Aline Schaefer (Building and Environment, 2025)

Full-spectrum Cannabis sativa extract enhances gut-peripheral organ integrity after experimental ischemic stroke - Solange de Souza Stork; Khiany Mathias; Fernanda Gava; Larissa Joaquim; David dos Santos; Anita Dal Bó Tiscoski; Sandra Bonfante; Yasmin Ribeiro Strickert; Richard Simon Machado; Helena Mafra Martins; Jéssica Schaefer Chaves; Jaqueline Generoso; et al. (Inflammopharmacology, 2025)

Ayahuasca Pretreatment Prevents Sepsis-Induced Anxiety-Like Behavior, Neuroinflammation, and Oxidative Stress, and Increases Brain-Derived Neurotrophic Factor - Rick Wilhiam de Camargo; Larissa Joaquim; Richard Simon Machado; Suelen de Souza Ramos; Lara Rodrigues da Rosa; Linério Ribeiro de Novais Junior; Khiany Mathias; Lara Maximiano; Yasmin Ribeiro Strickert; Rafael Nord; Maria Laura Gava; Eduarda Scarpari; et al. (Molecular Neurobiology, 2025)

Strong thermospheric response to the almost undetectable substorm on May 29, 2023 - Yongliang Zhang; Qian Wu; Wenbin Wang; Larry Paxton; Robert Schaefer; Dong Lin; Lying Qian; Haonan Wu; Kun Wu; Ying Zou; Martin Connors (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Eutrophic soils and weathering levels influence the distribution of seasonally dry forests in Brazil - Sara Ramos dos Santos; Carolina Malala Martins Souza; David Lukas de Arruda; Danilo de Lima Camêlo; Jairo Tronto; Greice Leal Pereira; Danilo Cesar de Mello; Wilson Tadeu Lopes da Silva; Liovando Marciano da Costa; Carlos Ernesto Gonçalves Reynaud Schaefer (Geoderma Regional, 2025)

Dashboard for interpreting future climate files used in the simulation of buildings – An outdoor thermal comfort approach - Igor Catão Martins Vaz; Enedir Ghisi; Liseane Padilha Thives; Abel Silva Vieira; Ricardo Forgiarini Rupp; Aline Schaefer; Rafael Almeida Flores; Matheus Bruhns Bastos; Deivis Luis Marinoski; Arthur Santos Silva; Max Weeber; Andrea Invidiata (Energy and Buildings, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Thermodegradation of organic matter in soils of different mineral composition in Brazil - Sara Ramos dos Santos; Liovando Marciano da Costa; Carolina Malala Martins Souza; Greice Pereira Leal; Danilo Cesar de Mello; Wilson Tadeu Lopes da Silva; Danilo de Lima Camêlo; Carlos Ernesto Gonçalves Reynaud Schaefer (Geoderma Regional, 2024)

The challenge of assessing the effects of drifting fish aggregating devices on the behaviour and biology of tropical tuna - Amaël Dupaix; Frédéric Ménard; John D. Filmalter; Yannick Baidai; Nathalie Bodin; Manuela Capello; Emmanuel Chassot; Hervé Demarcq; Jean‐Louis Deneubourg; Alain Fonteneau; Fabien Forget; Francesca Forrestal; et al. (Fish and Fisheries, 2024)
Fishers have intensively used drifting fish aggregating devices (DFADs) over the last three decades to facilitate their catch of tropical tunas. DFADs increase purse‐seine efficiency, potentially increasing tuna fishing mortality. They could also have impacts on tuna natural mortality and reproductive potential, and assessing the consequences of their presence at sea on tuna populations is a challenge. The use of DFADs results in a major increase in the number of floating objects, which are spatially heterogeneous at sea. To date, no converging scientific results exist regarding the effects of DFADs on the large‐scale movements and behaviour of tuna, mainly due to the difficulty of disentangling the respective roles of DFADs and environmental factors. Some biological indices show that tuna condition is lower when associated to a floating object than in a free‐swimming school. However, it is not clear whether this is the cause or the consequence of the association nor if it has long‐term effects on individuals' fitness. Further scientific progress requires (i) the collection of time series of indicators to monitor habitat change, individual behaviour, individual fitness, and population dynamics and (ii) experimental studies to identify the underlying behavioural and biological processes involved in associative behaviour. The extent of the modification of the surface habitat by the massive deployment of DFADs and the current uncertainty of the possible long‐term consequences on the individual fitness and dynamics of tuna populations argue for the need for increased awareness of this issue by Regional Fisheries Management Organisations regulating tuna fishing.

Configuration and timing of the postglacial marine incursion along the eastern Ungava Peninsula (Nunavik, Canada): implications for deglaciation models - Claudie Lefebvre‐Fortier; Martin Roy; Hugo Dubé‐Loubert; Etienne Brouard; Joerg M. Schaefer (Journal of Quaternary Science, 2024)
The final deglaciation stages of the Laurentide Ice Sheet in northern Quebec–Labrador were marked by the incursion of the d'Iberville Sea into the coastal areas of Ungava Bay. Remote and field mapping of raised marine strandlines along the Ungava Peninsula east coast show that the maximum marine limit decreases from south (165 m) to north (100 m), reflecting differential uplift linked to an ice mass remnant located to the southwest of the bay. Reconstruction of the uppermost marine limit in two east–west transects extending into the Peninsula interior reveals distinct sea‐level stands with limited extents towards the west, indicating that the early stages of the marine incursion occurred in contact with the ice margin. The reconstruction also identifies the maximum eastward extent of ice‐dammed lakes that occupied the Arnaud River and Aux‐Feuilles River valleys. 10 Be surface exposure dating of marine strandlines yielded consistent 10 Be ages that indicate a rapid deglaciation of Ungava Bay between 8900 ± 200 a (north) and 7900 ± 200 a (south). These results provide constraints on the position of the Labrador Sector eastern and western ice margins during the late deglaciation, in addition to the timing of ice and meltwater discharges from the Ungava Bay region.

Drug Dissolution in Oral Drug Absorption: Workshop Report - Kimberly Raines; Payal Agarwal; Patrick Augustijns; Alaadin Alayoubi; Lucas Attia; Annette Bauer-Brandl; Martin Brandl; Parnali Chatterjee; Hansong Chen; Yuly Chiang Yu; Carrie Coutant; Ana Luisa Coutinho; et al. (The AAPS Journal, 2023)
The in-person workshop “Drug Dissolution in Oral Drug Absorption” was held on May 23–24, 2023, in Baltimore, MD, USA. The workshop was organized into lectures and breakout sessions. Three common topics that were re-visited by various lecturers were amorphous solid dispersions (ASDs), dissolution/permeation interplay, and in vitro methods to predict in vivo biopharmaceutics performance and risk. Topics that repeatedly surfaced across breakout sessions were the following: (1) meaning and assessment of “dissolved drug,” particularly of poorly water soluble drug in colloidal environments ( e.g. , fed conditions, ASDs); (2) potential limitations of a test that employs sink conditions for a poorly water soluble drug; (3) non-compendial methods ( e.g. , two-stage or multi-stage method, dissolution/permeation methods); (4) non-compendial conditions ( e.g. , apex vessels, non-sink conditions); and (5) potential benefit of having both a quality control method for batch release and a biopredictive/biorelevant method for biowaiver or bridging scenarios. An identified obstacle to non-compendial methods is the uncertainty of global regulatory acceptance of such methods.

Aqueous-phase photo-oxidation of selected green leaf volatiles initiated by OH radicals: Products and atmospheric implications - Kumar Sarang; Tobias Otto; Sahir Gagan; Krzysztof Rudzinski; Thomas Schaefer; Martin Brüggemann; Irena Grgić; Adam Kubas; Hartmut Herrmann; Rafal Szmigielski (Science of The Total Environment, 2023)

Soilscapes and geoenvironments at Stansbury Peninsula, Nelson Island, maritime Antarctica - Martin Meier; Márcio Rocha Francelino; Arthur Stefanelli Gasparini; André Thomazini; Antônio Batista Pereira; Fernando Leopoldo von Krüger; Elpídio Inácio Fernandes-Filho; Carlos Ernesto Gonçalves Reynauld Schaefer (CATENA, 2023)

Inconclusive evidence that breathing shapes pupil dynamics in humans: a systematic review - Martin Schaefer; Sylvia Edwards; Frans Nordén; Johan N. Lundström; Artin Arshamian (Pflügers Archiv - European Journal of Physiology, 2023)
More than 50 years ago, it was proposed that breathing shapes pupil dynamics. This widespread idea is also the general understanding currently. However, there has been no attempt at synthesizing the progress on this topic since. We therefore conducted a systematic review of the literature on how breathing affects pupil dynamics in humans. We assessed the effect of breathing phase, depth, rate, and route (nose/mouth). We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, and conducted a systematic search of the scientific literature databases MEDLINE, Web of Science, and PsycInfo in November 2021. Thirty-one studies were included in the final analyses, and their quality was assessed with QualSyst. The study findings were summarized in a descriptive manner, and the strength of the evidence for each parameter was estimated following the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. The effect of breathing phase on pupil dynamics was rated as “low” (6 studies). The effect of breathing depth and breathing rate (6 and 20 studies respectively) were rated as “very low”. Breathing route was not investigated by any of the included studies. Overall, we show that there is, at best, inconclusive evidence for an effect of breathing on pupil dynamics in humans. Finally, we suggest some possible confounders to be considered, and outstanding questions that need to be addressed, to answer this fundamental question. Trial registration: This systematic review has been registered in the international prospective register of systematic reviews (PROSPERO) under the registration number: CRD42022285044.

Easy to assemble dielectric barrier discharge plasma ionization source based on printed circuit boards - Moritz Hitzemann; Christoph Schaefer; Ansgar T. Kirk; Alexander Nitschke; Martin Lippmann; Stefan Zimmermann (Analytica Chimica Acta, 2023)

Variability in mycorrhizal status of plant species is much larger within than between plots in grassland and coastal habitats - Martin Bitomský; Hanno Schaefer; Robin J. Pakeman; Jitka Klimešová; Lars Götzenberger; Martin Duchoslav (Oecologia, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Mycorrhizal status is a poor predictor of the distribution of herbaceous species along the gradient of soil nutrient availability in coastal and grassland habitats - Martin Bitomský; Robin J. Pakeman; Hanno Schaefer; Jitka Klimešová; Solvita Rūsiņa; Zdeňka Lososová; Pavla Mládková; Martin Duchoslav (Mycorrhiza, 2021)

Beyond ecosystem modeling: A roadmap to community cyberinfrastructure for ecological data‐model integration - Istem Fer; Anthony K. Gardella; Alexey N. Shiklomanov; Eleanor E. Campbell; Elizabeth M. Cowdery; Martin G. De Kauwe; Ankur Desai; Matthew J. Duveneck; Joshua B. Fisher; Katherine D. Haynes; Forrest M. Hoffman; Miriam R. Johnston; et al. (Global Change Biology, 2021)
In an era of rapid global change, our ability to understand and predict Earth's natural systems is lagging behind our ability to monitor and measure changes in the biosphere. Bottlenecks to informing models with observations have reduced our capacity to fully exploit the growing volume and variety of available data. Here, we take a critical look at the information infrastructure that connects ecosystem modeling and measurement efforts, and propose a roadmap to community cyberinfrastructure development that can reduce the divisions between empirical research and modeling and accelerate the pace of discovery. A new era of data‐model integration requires investment in accessible, scalable, and transparent tools that integrate the expertise of the whole community, including both modelers and empiricists. This roadmap focuses on five key opportunities for community tools: the underlying foundations of community cyberinfrastructure; data ingest; calibration of models to data; model‐data benchmarking; and data assimilation and ecological forecasting. This community‐driven approach is a key to meeting the pressing needs of science and society in the 21st century.

A mixed-methods approach to understanding perceptions of hepatitis B and hepatocellular carcinoma among ethnically diverse Black communities in South Florida - Patricia Jones; Joselin Soler; Natasha Schaefer Solle; Paul Martin; Erin Kobetz (Cancer Causes & Control, 2020)

Low-cost UAV surveys of hurricane damage in Dominica: automated processing with co-registration of pre-hurricane imagery for change analysis - Martin Schaefer; Richard Teeuw; Simon Day; Dimitrios Zekkos; Paul Weber; Toby Meredith; Cees J. van Westen (Natural Hazards, 2020)
In 2017, hurricane Maria caused unprecedented damage and fatalities on the Caribbean island of Dominica. In order to ‘build back better’ and to learn from the processes causing the damage, it is important to quickly document, evaluate and map changes, both in Dominica and in other high-risk countries. This paper presents an innovative and relatively low-cost and rapid workflow for accurately quantifying geomorphological changes in the aftermath of a natural disaster. We used unmanned aerial vehicle (UAV) surveys to collect aerial imagery from 44 hurricane-affected key sites on Dominica. We processed the imagery using structure from motion (SfM) as well as a purpose-built Python script for automated processing, enabling rapid data turnaround. We also compared the data to an earlier UAV survey undertaken shortly before hurricane Maria and established ways to co-register the imagery, in order to provide accurate change detection data sets. Consequently, our approach has had to differ considerably from the previous studies that have assessed the accuracy of UAV-derived data in relatively undisturbed settings. This study therefore provides an original contribution to UAV-based research, outlining a robust aerial methodology that is potentially of great value to post-disaster damage surveys and geomorphological change analysis. Our findings can be used (1) to utilise UAV in post-disaster change assessments; (2) to establish ground control points that enable before-and-after change analysis; and (3) to provide baseline data reference points in areas that might undergo future change. We recommend that countries which are at high risk from natural disasters develop capacity for low-cost UAV surveys, building teams that can create pre-disaster baseline surveys, respond within a few hours of a local disaster event and provide aerial photography of use for the damage assessments carried out by local and incoming disaster response teams.

Secondary forest fragments offer important carbon and biodiversity cobenefits - Fabio A. R. Matos; Luiz F. S. Magnago; Carlos Aquila Chan Miranda; Luis F. T. de Menezes; Markus Gastauer; Nathália V. H. Safar; Carlos E. G. R. Schaefer; Mônica P. da Silva; Marcelo Simonelli; Felicity A. Edwards; Sebastião V. Martins; João A. A. Meira‐Neto; et al. (Global Change Biology, 2020)
Tropical forests store large amounts of carbon and high biodiversity, but are being degraded at alarming rates. The emerging global Forest and Landscape Restoration (FLR) agenda seeks to limit global climate change by removing carbon dioxide from the atmosphere through the growth of trees. In doing so, it may also protect biodiversity as a free cobenefit, which is vital given the massive shortfall in funding for biodiversity conservation. We investigated whether natural forest regeneration on abandoned pastureland offers such cobenefits, focusing for the first time on the recovery of taxonomic diversity (TD), phylogenetic diversity (PD) and functional diversity (FD) of trees, including the recovery of threatened and endemic species richness, within isolated secondary forest (SF) fragments. We focused on the globally threatened Brazilian Atlantic Forest, where commitments have been made to restore 1 million hectares under FLR. Three decades after land abandonment, regenerating forests had recovered ~20% (72 Mg/ha) of the above‐ground carbon stocks of a primary forest (PF), with cattle pasture containing just 3% of stocks relative to PFs. Over this period, SF recovered ~76% of TD, 84% of PD and 96% of FD found within PFs. In addition, SFs had on average recovered 65% of threatened and ~30% of endemic species richness of primary Atlantic forest. Finally, we find positive relationships between carbon stock and tree diversity recovery. Our results emphasize that SF fragments offer cobenefits under FLR and other carbon‐based payments for ecosystem service schemes (e.g. carbon enhancements under REDD+). They also indicate that even isolated patches of SF could help to mitigate climate change and the biodiversity extinction crisis by recovering species of high conservation concern and improving landscape connectivity.

21st century toolkit for optimizing population health through precision nutrition - Aifric O'Sullivan; Bethany Henrick; Bonnie Dixon; Daniela Barile; Angela Zivkovic; Jennifer Smilowitz; Danielle Lemay; William Martin; J. Bruce German; Sara Elizabeth Schaefer (Critical Reviews in Food Science and Nutrition, 2018)

A novel biological function of soluble biglycan: Induction of erythropoietin production and polycythemia - Helena Frey; Kristin Moreth; Louise Tzung-Harn Hsieh; Jinyang Zeng-Brouwers; Birgit Rathkolb; Helmut Fuchs; Valérie Gailus-Durner; Renato V. Iozzo; Martin Hrabě de Angelis; Liliana Schaefer (Glycoconjugate Journal, 2017)

Does flower and fruit conspicuousness affect plant fitness? Contrast, color coupling and the interplay of pollination and seed dispersal in two Vaccinium species - Kalliope E. Stournaras; H. Martin Schaefer (Evolutionary Ecology, 2017)

Bait worms: a valuable and important fishery with implications for fisheries and conservation management - Gordon J Watson; Joanna M Murray; Martin Schaefer; Adam Bonner (Fish and Fisheries, 2017)
Bait is an integral part of coastal life, but is perceived as a low‐value resource as fisheries are data‐limited, locally focussed and largely unregulated even though the ecological impacts of collection are considerable. An empirical assessment of three UK‐based ragworm fisheries combined with an analysis of published literature has produced the first global assessment of polychaete bait fisheries. The five most expensive (retail price per kg) marine species sold on the global fisheries market are polychaetes ( Glycera dibranchiata , Diopatra aciculata , Nereis ( Alitta ) virens , Arenicola defodiens and Marphysa sanguinea ). We estimate that 1600 t of N. virens per annum (worth £52 million) are landed in the UK with approximately 121 000 tonnes of polychaetes collected globally valued at £5.9 billion. Using remote closed circuit television (CCTV) cameras to monitor collectors, activity at local sites is considerable with a mean of 3.14 collectors per tide (day and night) at one site and individuals digging for up to 3 h per tide, although intensity differed seasonally and between sites. Collectors removed on average 1.4 kg of N. virens per person per hour, walking a considerable distance across the intertidal sediment to reach areas that were usually already dug. The implications of these human activity and biomass removal levels are explored in the context of fisheries and conservation management. At local, regional and national scales, polychaete bait fisheries are highly valuable, extract significant biomass and have considerable impacts; therefore, they urgently require governance equivalent to other fisheries.

Decline in territory size and fecundity as a response to carrying capacity in an endangered songbird - Stefanie A. Hartmann; Steffen Oppel; Gernot Segelbacher; Mery E. Juiña; H. Martin Schaefer (Oecologia, 2017)

N-3 vs. n-6 fatty acids differentially influence calcium signalling and adhesion of inflammatory activated monocytes: impact of lipid rafts - Martina Barbara Schaefer; Christian Alexander Schaefer; Stefanie Schifferings; Christoph Rüdiger Wolfram Kuhlmann; Annett Urban; Utz Benscheid; Tobias Fischer; Matthias Hecker; Rory E. Morty; Istvan Vadasz; Susanne Herold; Martin Witzenrath; et al. (Inflammation Research, 2016)

Avian haemosporidian parasites in an urban forest and their relationship to bird size and abundance - Diego Santiago-Alarcon; Ian MacGregor-Fors; Katharina Kühnert; Gernot Segelbacher; H. Martin Schaefer (Urban Ecosystems, 2016)

Land use intensification alters ecosystem multifunctionality via loss of biodiversity and changes to functional composition - Eric Allan; Pete Manning; Fabian Alt; Julia Binkenstein; Stefan Blaser; Nico Blüthgen; Stefan Böhm; Fabrice Grassein; Norbert Hölzel; Valentin H. Klaus; Till Kleinebecker; E. Kathryn Morris; et al. (Ecology Letters, 2015)
Global change, especially land‐use intensification, affects human well‐being by impacting the delivery of multiple ecosystem services (multifunctionality). However, whether biodiversity loss is a major component of global change effects on multifunctionality in real‐world ecosystems, as in experimental ones, remains unclear. Therefore, we assessed biodiversity, functional composition and 14 ecosystem services on 150 agricultural grasslands differing in land‐use intensity. We also introduce five multifunctionality measures in which ecosystem services were weighted according to realistic land‐use objectives. We found that indirect land‐use effects, i.e. those mediated by biodiversity loss and by changes to functional composition, were as strong as direct effects on average. Their strength varied with land‐use objectives and regional context. Biodiversity loss explained indirect effects in a region of intermediate productivity and was most damaging when land‐use objectives favoured supporting and cultural services. In contrast, functional composition shifts, towards fast‐growing plant species, strongly increased provisioning services in more inherently unproductive grasslands.

Fruit advertisement strategies in two Neotropical plant–seed disperser markets - Kalliope E. Stournaras; Richard O. Prum; H. Martin Schaefer (Evolutionary Ecology, 2015)

Flower colours in temperate forest and grassland habitats: a comparative study - Julia Binkenstein; H. Martin Schaefer (Arthropod-Plant Interactions, 2015)

Unexplored Brazilian oceanic island host high salt tolerant biosurfactant-producing bacterial strains - Fábio Sérgio Paulino da Silva; Victor Satler Pylro; Pericles Leonardo Fernandes; Gisele Souza Barcelos; Karlos Henrique Martins Kalks; Carlos Ernesto Gonçalves Reynaud Schaefer; Marcos Rogério Tótola (Extremophiles, 2015)

Genetic depletion at adaptive but not neutral loci in an endangered bird species - Stefanie A. Hartmann; H. Martin Schaefer; Gernot Segelbacher (Molecular Ecology, 2014)
Many endangered species suffer from the loss of genetic diversity, but some populations may be able to thrive even if genetically depleted. To investigate the underlying genetic processes of population bottlenecks, we apply an innovative approach for assessing genetic diversity in the last known population of the endangered Pale‐headed Brushfinch ( Atlapetes pallidiceps ) in Ecuador. First, we measure genetic diversity at eleven neutral microsatellite loci and adaptive SNP variation in five Toll‐like receptor ( TLR ) immune system genes. Bottleneck tests confirm genetic drift as the main force shaping genetic diversity in this species and indicate a 99 % reduction in population size dating back several hundred years. Second, we compare contemporary microsatellite diversity with historic museum samples of A. pallidiceps , finding no change in genetic diversity. Third, we compare genetic diversity in the Pale‐headed Brushfinch with two co‐occurring‐related brushfinch species ( Atlapetes latinuchus, Buarremon torquatus ), finding a reduction of up to 91% diversity in the immune system genes but not in microsatellites. High TLR diversity is linked to decreased survival probabilities in A. pallidiceps . Low TLR diversity is thus probably an adaptation to the specific selection regime within its currently very restricted distribution (approximately 200 ha), but could severely restrict the adaptive potential of the species in the long run. Our study illustrates the importance of investigating both neutral and adaptive markers to assess the effect of population bottlenecks and for recommending specific management plans in endangered species.

Functional relationships beyond species richness patterns: trait matching in plant–bird mutualisms across scales - D. Matthias Dehling; Till Töpfer; H. Martin Schaefer; Pedro Jordano; Katrin Böhning‐Gaese; Matthias Schleuning (Global Ecology and Biogeography, 2014)
Aim Functional relationships between species groups on macroecological scales have often been inferred from comparisons of species numbers across space. On large spatial scales, however, it is difficult to assess whether correlations of species numbers represent actual functional relationships. Here, we investigated the functional relationship between a feeding guild (fruit‐eating birds) and its resource (fleshy‐fruited plants) by studying the matching of their functional traits across spatial scales, from individual interactions to regional patterns. Location A 3000‐m elevational gradient in the tropical A ndes. Methods We sampled plant–bird interactions at two sites along the elevational gradient, and using multivariate statistics (fourth‐corner analysis) we identified corresponding morphological traits of birds and plants that influenced which bird species fed from which plant species. We then tested whether the functional trait diversities of the bird species assemblages matched those of the plant species assemblages along the elevational gradient. Results Corresponding functional traits of birds and plants were closely and significantly correlated on the scale of individual plant–bird interactions. On the regional scale, the functional diversities, but not species numbers, of bird and plant assemblages correlated significantly along the elevational gradient. Main conclusions The analysis of species interaction networks with multivariate statistics was a powerful tool for identifying relationships between functional traits of interacting species. The close functional relationships between birds and plants on the scale of individual interactions and on the regional scale show that comparisons of functional trait diversities, based on matching traits of interacting species, are better suited than correlations of species numbers to reveal the mechanisms behind large‐scale diversity patterns of interacting species. The identification of functional interdependences between interacting species on large spatial scales will be important for improving predictive models of species distributions in space and time.

Development of 12 microsatellite loci for the endangered Pale-headed Brushfinch (Atlapetes pallidiceps) and their cross-amplification in two co-occurring Brushfinches - Stefanie A. Hartmann; H. Martin Schaefer; Gernot Segelbacher (Journal of Ornithology, 2014)

Food allocation rules vary with age and experience in a cooperatively breeding parrot - Nadine Klauke; Jeroen Jansen; Jos Kramer; H. Martin Schaefer (Behavioral Ecology and Sociobiology, 2014)

Limits of selection against cheaters: birds prioritise visual fruit advertisement over taste - Zhen Wang; H. Martin Schaefer (Oecologia, 2014)

Increasing land-use intensity decreases floral colour diversity of plant communities in temperate grasslands - Julia Binkenstein; Julien P. Renoult; H. Martin Schaefer (Oecologia, 2013)

Game theory, multi-modal signalling and the evolution of communication - Graeme D. Ruxton; H. Martin Schaefer (Behavioral Ecology and Sociobiology, 2013)

Garden Warbler, Sylvia borin, detect carotenoids in food but differ strongly in individual food choice - Carlo Catoni; Benjamin Metzger; H. Martin Schaefer; Franz Bairlein (Journal of Ornithology, 2011)

Fruit size, crop mass, and plant height explain differential fruit choice of primates and birds - Martina Flörchinger; Julius Braun; Katrin Böhning-Gaese; H. Martin Schaefer (Oecologia, 2010)

Spring arrival along a migratory divide of sympatric blackcaps (Sylvia atricapilla) - Gregor Rolshausen; Keith A. Hobson; H. Martin Schaefer (Oecologia, 2010)

Reliable cues and signals of fruit quality are contingent on the habitat in black elder ( Sambucus nigra ) - H. Martin Schaefer; Julius Braun (Ecology, 2009)
Communication mediates interactions between organisms and can be based on signals or cues. Signals are selected for their signaling function, whereas cues evolve for reasons other than signaling. To be evolutionarily stable, communication needs to be reliable on average, but the mechanisms that enforce reliability are hotly debated in light of strong environmental influence on signals and cues. While fruit quality in black elder ( Sambucus nigra ) is unrelated to fruit color, it is indicated by alternative pedicel phenotypes. Information on fruit quality has thus been transferred from the fruit to the developmentally associated pedicels, which are environmentally determined cues. Within each phenotype, color variation indicates fruit quality. Communication by black elder is thus reliable, but the proximate mechanisms enforcing reliability are habitat specific. High irradiance increases both the contrasts of the visual cue and fruit quality in the anthocyanin‐based red pedicel phenotype, while shaded plants of the chlorophyll‐based green phenotype apparently use signals by forgoing photosynthesis. This is because lower chlorophyll content in green pedicels creates contrasting pedicels, and higher contrasts indicate higher sugar content in the fruits of green pedicels. Because anthocyanins are light‐induced, plants use cues when exposed to high irradiance, whereas they apparently use costly signals in the shade by reducing chlorophyll content in the pedicels. In behavioral field and laboratory experiments we document that avian seed dispersers select among pedicel phenotypes that indicate different fruit quality. Plants can thus increase their reproductive success by sending highly informative cues. Our results indicate how reliable information transfer can be maintained both in cues and signals in spite of substantial environmental influence on visual traits.

Geographic patterns in fruit colour diversity: do leaves constrain the colour of fleshy fruits? - Kevin C. Burns; Eliana Cazetta; Mauro Galetti; Alfredo Valido; H. Martin Schaefer (Oecologia, 2009)

Why are fruits colorful? The relative importance of achromatic and chromatic contrasts for detection by birds - Eliana Cazetta; Hinrich Martin Schaefer; Mauro Galetti (Evolutionary Ecology, 2009)

Does attraction to frugivores or defense against pathogens shape fruit pulp composition? - Eliana Cazetta; H. Martin Schaefer; Mauro Galetti (Oecologia, 2008)

Do aphids paint the tree red (or yellow)—can herbivore resistance or photoprotection explain colourful leaves in autumn? - Gregor Rolshausen; H. Martin Schaefer (Plant Ecology, 2007)

The fruits of selectivity: how birds forage on Goupia glabra fruits of different ripeness - H. Martin Schaefer; Veronika Schaefer (Journal of Ornithology, 2006)

The progesterone derivative dydrogesterone down-regulates neurokinin 1 receptor expression on lymphocytes, induces a Th2 skew and exerts hypoalgesic effects in mice - Arif Suphi Orsal; Sandra Blois; Dominika Labuz; Eva M. J. Peters; Martin Schaefer; Petra C. Arck (Journal of Molecular Medicine, 2006)